Localization and regulation of c-fos and c-jun protooncogene induction by systolic wall stress in normal and hypertrophied rat hearts. - Schunkert, H (1991)
The effect of changes in left ventricular (LV) systolic force generation on cardiac c-fos and c-jun protooncogene expression was studied by using isolated beating hearts from male Wistar rats. An isovolumic buffer-perfused heart preparation was utilized in which coronary flow and heart rate were held constant and increments in LV balloon volume were used to generate defined levels of LV systolic wall stress. Using Northern and slot-blot analyses, we found that LV tissue from control hearts that generated high levels of LV systolic wall stress expressed 3- to 4.4-fold higher c-fos and c-jun mRNA levels in comparison with tissue from the respective flaccid right ventricles, and in comparison with LV tissue from hearts that generated minimal LV systolic wall stress. To distinguish the role of passive LV diastolic wall stretch from active LV force generation, we found that distension of the LV balloon per se did not have a significant effect on protooncogene induction in hearts perfused with 2,3-butanedione monoxime, which prevents systolic cross-bridge cycling and force generation. In additional hearts studied at a constant LV balloon volume to generate an LV end-diastolic pressure of 10 mm Hg, c-fos mRNA levels were proportional to the magnitude of peak LV systolic wall stress (r = 0.823, P less than 0.05). In these protocols, Fos protein was localized by immunohistochemistry in myocyte nuclei with minimal staining in fibroblasts and vascular smooth muscle. When c-fos and c-jun mRNA expression was compared in hearts with chronic LV hypertrophy due to ascending aortic banding and age-matched control hearts that generated similar incremental levels of LV systolic wall stress, significantly lower levels of c-fos and c-jun mRNA were measured in the hypertrophied hearts. However, there was no difference in protooncogene mRNA expression in response to stimulation by the Ca2+ ionophore A23187. These data suggest that, in this isolated isovolumic beating heart preparation, the active generation of an acute increment in LV systolic force independent of passive diastolic myocardial stretch causes a rapid induction of both c-fos and c-jun, which is down-regulated in the presence of established LV hypertrophy.